PERAN KOMITMEN ORGANISASI DAN SATUAN KERJA PERANGKAT DAERAH DALAM MEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Wardani Yasa, Si Made Ayu Sri; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
This study was conducted to determine the effect of budgetary participation on budgetary slack in local government Tabanan. The aim of research to examine the effect of budgetary participation on budgetary slack and organizational commitment and characteristics on SKPD as a moderating variable in Tabanan Regency Government. This study was conducted in 41 SKPD in Tabanan Regency. Sampling was done by nonprobability sampling method with saturated sampling technique. Data was collected by survey. The dependent variable in this study is the budgetary slack and the independent variable was the participation of budgeting as well as moderating variable is the commitment of organizations and SKPD characteristics. Respondents are 123 people in the district goverment officials Tabanan who participated in the preparation of the budget. Data were analyzed with regression moderation by the method of interaction (Moderated Regression Analysis/MRA). The results show budgetary participation influence on budgetary slack. Organizational commitment does not moderate the effect of budgetary participation on budgetary slack. SKPD characteristics moderate the effect of budgetary participation on budgetary slack. Supervision and monitoring should be done to anticipate budgetary slack
Keywords: participation of budgeting, organizational commitment, SKPD characteristics, Tabanan Regency